How small wine Italian company from Puglia can enter the Chinese-Shanghai market - Tramacere, Andrea (2016)
This paper encompasses the strategy for small-medium wine companies from Puglia (Italy) to enter the Chinese market. The study was conducted to understand the reasons why the excellent quality wine from Puglia has no penetration in the Chinese market. The research took into consideration the position in terms of production, size and exports in the world of Italian producers from Puglia and their competitors in China. After analysing the market and the opportunities, the report develops a strategy of cooperation among the companies to obtain more resources and more power in order to better approach this enormous and difficult market.